EXTRACTING THE PREVALENCE OF FRAILTY AMONG THE GERIATRIC POPULATION RESIDING IN AURANGABAD DISTRICT – A CROSS-SECTIONAL STUDY. - Dr Rudalee Husale; Dr Sachin Maghade; Swamini Bhoir; Priyanka Tripathi; Apeksha Toshniwal (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
BACHGROUND: In India, there are roughly 10.4 crore senior people, with rural areas housing 65% of them. Rural locations have limited access to healthcare. Frailty is characterised by a gradual loss of reserve and capacity for adaptation along with a general decline in health.Accessibility to healthcare is limited in rural areas. Primary care physicians deal with a fairly large number of patients from the geriatric age group. Our study’s goal was to find out how common frailty was among the elderly population in the Aurangabad area. METHODS:104 participants in an observational study at a geriatric care centre in the Aurangabad area of Maharashtra, India, were chosen using convenient sampling, and the prevalence of the condition was determined using the Frailty Aging Index. RESULT: Prevalence of frailty in non frail was 22.11%(1-2 indicates no frailty) , in pre-frail it was 32.69% (3-4 indicates frailty risk) and frail it was 45.19% (≥7 indicates frailty ). CONCLUSION: The elderly population appears frailty. Their health will improve as a result of health programs that target the prevention, early identification, and treatment of morbidities and frailty.